Prophet Tradition Against Fake News: Formulation of Fake News Examination Method Based on Ulum Al-Hadits - M. Dede Rodliyana (International Journal of Nusantara Islam, 2022)
The spread of fake news through social media has become a global problem and presents disorientation of knowledge or post-truth. This study aims to reveal the Jarh al-Ta'dil formula in spreading fake news. From this research, the Qur'an instructs Muslims to verify the source of all information they receive before believing it to be true:' (QS. Al-hujurat: 6). Muslims should not act on unverified sources and must legalize all information. Islam prohibits Muslims from sharing unverified information. When receiving it with your tongue and saying with your mouth what you do not know and take for granted, it is extraordinary in the sight of Allah. The formulation of the ulumul hadith method for dealing with recent fake news Several methods of criticizing fake news resulted from this hadith critique method